An electrolyte for electrolytic copper foil and its preparation method and application

By optimizing the electrolyte formulation, uniformly sized, dense and fine grains were prepared to inhibit the generation of transition layers, and the tensile strength, elongation and warpage problems of 6μm electrolytic copper foil at low cost were solved, and high-performance electrolytic copper foil production was achieved.

CN117127225BActive Publication Date: 2025-04-29GUANGDONG YINGHUA ELECTRONIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311185510.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-04-29
Estimated Expiration
2043-09-13

AI Technical Summary

Technical Problem

The prior art is difficult to achieve a tensile strength of the 6 μm electrolytic copper foil at a low cost while achieving a room temperature of 450 MPa or more, an elongation of ≥6%, and a warpage of ≤10 mm.

Method used

By adopting a specific electrolyte formulation, including 90-110g/L Cu2+, 110-130g/L H2SO4, additive 1 and additive 2, the ratio of additive 1 and additive 2 is optimized to prepare uniform, dense and fine grains, effectively inhibiting the generation of transition layers.

Benefits of technology

The tensile strength and elongation of the electrolytic copper foil are achieved in compliance with the standards, with a warpage of ≤10mm, solving the problems of high cost and poor performance in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117127225B_ABST
    Figure CN117127225B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of electrolytic copper foil preparation, and specifically discloses an electrolyte for electrolytic copper foil, a preparation method and an application thereof. The electrolyte comprises 90 - 110 g / L of Cu 2+ , 110 - 130 g / L of H2SO4, additive 1, additive 2 and a solvent. The additive 1 comprises Cl ‑ and Ni 2+ ; The additive 2 comprises sodium polydithiopropanesulfonate, sodium N,N-dimethyl-dithiocarbamoyl propanesulfonate, sulfonamide, gelatin, hydroxyethyl cellulose and polyethylene glycol. The electrolytic copper foil prepared by the electrolyte and production process of the present invention has high room temperature tensile strength and elongation, a warpage degree ≤ 10 mm, uniform dimensions, can inhibit the generation of the transition layer of the electrolytic copper foil, and brings new development opportunities to the electrolytic copper foil manufacturing industry and even the lithium battery manufacturing industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytic copper foil preparation, and in particular relates to an electrolyte for electrolytic copper foil and a preparation method and application thereof. Background Art

[0002] Electrolytic copper foil is widely used in various fields such as printed circuit boards and negative electrode collectors of lithium-ion secondary batteries. As the negative electrode current collector of lithium batteries, electrolytic copper foil supports the negative electrode active materials in lithium batteries and collects and conducts electrons passing through the negative electrode materials of lithium batteries. Electrolytic copper foil will bring huge market demand with the development of lithium batteries in new energy, consumer electronics, energy storage and other fields.

[0003] During the charging and discharging process of lithium batteries, the embedding and de-embedding of lithium ions in the negative electrode material will cause the negative electrode material to undergo a certain degree of recoverable expansion and contraction, that is, reversible deformation. The stress caused by this deformation will be correspondingly transmitted to the electrolytic copper foil as the negative electrode current collector. If the tensile strength and elongation of the electrolytic copper foil are low, the deformation of the negative electrode material will easily lead to irreversible deformation of the electrolytic copper foil, that is, the electrolytic copper foil is prone to cracks, resulting in poor contact performance between the electrolytic copper foil and the active material, and thus poor collection and conduction of electrons. Therefore, the electrolytic copper foil for lithium batteries is required to have good tensile strength and elongation to avoid the breakage of the electrolytic copper foil caused by the deformation caused by the charging and discharging of the lithium battery, thereby increasing the safety of the lithium battery during use. In the prior art, the production process of the electrolyte and / or the electrolytic copper foil is used to improve the tensile strength and elongation of the electrolytic copper foil for lithium batteries. For example, Chinese patent application CN116180164A discloses a composite additive for ultra-thin electrolytic copper foil with ultra-high tensile strength and a method for preparing electrolytic copper foil using the additive, wherein the additive comprises four types: brightener, leveler, surfactant and high resistance agent; the brightener is at least one of sodium polydisulfide propane sulfonate, sodium N,N-dimethyldithiocarboxamide propane sulfonate, sodium thiol propane sulfonate, sodium hydroxymethyl sulfonate and isothiourea propane sulfonic acid inner salt; the leveler is gelatin or collagen, and its The molecular weight is 1000-3000MW; the surfactant is at least one of polyethylene glycol, polyimide, polyethylene oxide and hydroxyethyl cellulose; the high resistance agent is WG, which exists in the form of an aqueous solution; the additive can be used to prepare a double-sided light lithium battery copper foil with a thickness of 5-8μm, and its tensile strength can exceed 600MPa, and by adjusting the amount of additives, the tensile strength of the copper foil can be controlled in the range of 350-650MPa, achieving full coverage of multi-level tensile strength products. However, when the thickness of the above-mentioned electrolytic copper foil reaches an ultra-thin level of ≤6μm, under the premise of unchanged thickness, as the grain size decreases, the tensile strength of the electrolytic copper foil will increase, but the elongation will decrease as the grain size decreases. In the prior art, in order to obtain electrolytic copper foil for lithium batteries of ≤6μm with higher tensile strength and elongation, higher tensile strength and elongation are often achieved by refining the grains to a certain extent and regulating the uniformity of the grain size.

[0004] When direct current electroplating is performed on a titanium-based cathode roller using a copper sulfate electrolyte, the deposited ultra-thin electrolytic copper foil will always generate a transition layer near the titanium substrate, and the transition layer is composed of fine equiaxed nano-twin grains. Although the transition layer copper foil can accelerate the attachment and growth of copper crystal nuclei and accelerate the efficiency of electrodeposition, the presence of the transition layer will reduce the tensile strength and elongation of the electrolytic copper foil, and will produce a high warpage, which is not conducive to the subsequent slitting and coating of negative electrode materials of the electrolytic copper foil. Annealing treatment is often required to reduce the influence of the transition layer to increase the elongation. Although annealing treatment can reduce the warpage of the electrolytic copper foil and increase the elongation, it will cause the uniformity of the grain size to deteriorate, thereby affecting the tensile strength of the electrolytic copper foil, and the annealing treatment cost is relatively high. Therefore, it is difficult for the 6μm electrolytic copper foil produced in the prior art to achieve a room temperature tensile strength of more than 450MPa at low cost, an elongation of ≥6%, and a warpage of ≤10mm.

[0005] For 6μm electrolytic copper foil for lithium batteries, if the electrolyte used in the electrolysis process can regulate the grain size and uniformity and inhibit the formation of the transition layer, so that the room temperature tensile strength is stabilized at above 450MPa, the elongation is above 6% and the warpage is reduced to below 10mm, it will bring new development opportunities to the electrolytic copper foil manufacturing industry and even the lithium battery manufacturing industry. Summary of the invention

[0006] As used herein, the singular forms "a," "an," and "the" include both singular and plural referents unless the context clearly dictates otherwise. Numerical ranges recited by endpoints include all numbers and fractions within the corresponding ranges, as well as the recited endpoints.

[0007] The present invention aims at solving the problems in the prior art and provides an electrolyte for electrolytic copper foil and a preparation method and application thereof.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] In one aspect, the present invention provides an electrolyte for electrolytic copper foil, comprising 90-110 g / L of Cu 2+ , 110-130g / L H2SO4, additive 1, additive 2 and solvent.

[0010] Preferably, the additive 1 comprises Cl - and Ni 2+ The additive 2 includes sodium polydisulfide propane sulfonate, sodium N,N-dimethyl-dithiocarboxamide propane sulfonate, sulfonamide, gelatin, hydroxyethyl cellulose and polyethylene glycol.

[0011] Preferably, the additive 1 includes 0.5-1.5 mg / L of Cl -and 40-60 mg / L Ni 2+ .

[0012] Preferably, the additive 2 includes 20-26 mg / L of sodium polydisulfide propane sulfonate, 10-13 mg / L of sodium N,N-dimethyl-dithiocarboxamide propane sulfonate, 10-13 mg / L of sulfonamide, 40-52 mg / L of gelatin, 20-26 mg / L of hydroxyethyl cellulose and 20-26 mg / L of polyethylene glycol.

[0013] Preferably, the mass ratio of (sodium polydisulfide propane sulfonate + sodium N,N-dimethyl-disulfide propane sulfonate + sulfonamide): gelatin: (hydroxyethyl cellulose + polyethylene glycol) is 1:1:1.

[0014] Preferably, Ni in additive 1 2+ The mass ratio with additive 2 is 0.3-0.5:1.

[0015] Preferably, the Cu 2+ Selected from copper wire, copper rod, copper block or copper powder; the solvent is ultrapure water.

[0016] Preferably, the Cl - Selected from hydrochloric acid; the Ni 2+ At least one selected from the group consisting of nickel sulfate hexahydrate, nickel chloride hexahydrate, nickel oxide and nickel hydroxide.

[0017] Preferably, the molecular weight of the gelatin is 10000Da-50000Da.

[0018] The present invention also provides a method for preparing the above electrolyte, comprising Cu 2+ React with H2SO4 to obtain a primary copper sulfate electrolyte, which is filtered and mixed with additive 1 to obtain a secondary electrolyte, and then mixed with additive 2 after maintaining high temperature to obtain the electrolyte.

[0019] On the other hand, the present invention provides a use of the above-mentioned electrolyte or the electrolyte prepared by the above-mentioned preparation method in preparing electrolytic copper foil for lithium batteries.

[0020] The present invention also provides an electrolytic copper foil prepared from the above electrolyte.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The electrolyte of the present invention adopts specific additives 1 and additives 2, and optimizes the ratio of each component of additives 1 and additives 2 to obtain uniform, dense and fine grains, and effectively inhibit the generation of transition layers of electrolytic copper foil. The electrolytic copper foil prepared by the electrolyte and production process of the present invention has been measured to have room temperature tensile strength and elongation that meet the standards, and a warpage of ≤10 mm. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 BC diagram and IPF diagram of the cross section of the electrolytic copper foil prepared in Example 1 of the present invention;

[0024] Figure 2 BC diagram and IPF diagram of the cross section of the electrolytic copper foil prepared in Example 2 of the present invention;

[0025] Figure 3 BC diagram and IPF diagram of the cross section of the electrolytic copper foil prepared in Example 3 of the present invention;

[0026] Figure 4 The BC diagram and IPF diagram of the cross section of the electrolytic copper foil prepared in Comparative Example 1 of the present invention, wherein the dotted line box indicates the presence of a transition layer;

[0027] Figure 5 BC diagram and IPF diagram of the cross section of the electrolytic copper foil prepared in Comparative Example 2 of the present invention;

[0028] Figure 6 BC diagram and IPF diagram of the cross section of the electrolytic copper foil prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0029] The present invention is described below through specific embodiments to make the technical solution of the present invention easier to understand and grasp, but the present invention is not limited thereto, and the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments.

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention. The experimental methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0032] Example 1 An electrolyte for electrolytic copper foil

[0033] Includes the following components: 100g / L Cu 2+ , 120g / L H2SO4, additive 1, additive 2 and solvent water.

[0034] The additive 1 includes 0.5 mg / L Cl - , 40mg / L Ni 2+ and solvent; the Cl - is hydrochloric acid, Ni 2+ It is nickel chloride hexahydrate.

[0035] The additive 2 includes: 20 mg / L sodium polydisulfide propane sulfonate, 10 mg / L sodium N,N-dimethyl-dithiocarboxamide propane sulfonate, 10 mg / L sulfonamide, 40 mg / L gelatin (molecular weight 10000-50000 Da), 20 mg / L hydroxyethyl cellulose, 20 mg / L polyethylene glycol and a solvent.

[0036] The production process of the above electrolyte for producing 6μm high elongation electrolytic copper foil for lithium batteries is as follows:

[0037] Step 1, preparation of electrolyte: put a copper rod in a copper dissolving tank, add sulfuric acid from the top of the copper rod from top to bottom, and use a blower to blow high-temperature air from the bottom to top of the copper rod to obtain a primary copper sulfate electrolyte; after filtering the primary copper sulfate electrolyte, add additive 1 and mix to obtain a secondary electrolyte; the secondary electrolyte is maintained at a temperature of 50° C. through a heat exchanger, and is transported to a high-level tank and mixed evenly with the additive 2 solution to obtain an electrolyte, and the electrolyte is pumped into an electrolytic cell for electrolysis.

[0038] Step 2: Electrolytic preparation of green foil: at 50°C and 65A / dm 2 The raw foil is prepared by electrolysis in an electrolytic cell at a current density of .

[0039] Step 3, raw foil surface treatment: The prepared raw foil is subjected to conventional passivation treatment to obtain uncut finished electrolytic copper foil for lithium batteries. The conventional treatment uses a passivation solution containing 110 mg / L chromic anhydride, 220 mg / L glucose and RO water, the pH of the passivation solution is 3.4, the passivation treatment temperature is 32°C, and the passivation treatment current is 2A / dm 2 .

[0040] Example 2 An electrolyte for electrolytic copper foil

[0041] Includes the following components: 90g / L Cu 2+ , 110g / L H2SO4, additive 1, additive 2 and solvent water.

[0042] The additive 1 includes 1.5 mg / L of Cl - , 60mg / L Ni 2+ and solvent; the Cl - is hydrochloric acid, Ni 2+ It is nickel oxide.

[0043] The additive 2 includes: 24 mg / L sodium polydisulfide propane sulfonate, 12 mg / L sodium N,N-dimethyl-dithiocarboxamide propane sulfonate, 12 mg / L sulfonamide, 48 mg / L gelatin (molecular weight 10000-50000 Da), 24 mg / L hydroxyethyl cellulose, 24 mg / L polyethylene glycol and a solvent.

[0044] The production process of the above electrolyte for producing 6μm high elongation electrolytic copper foil for lithium batteries is as follows:

[0045] Step 1, preparation of electrolyte: put copper wire in the copper dissolving tank, add sulfuric acid from the top of the copper wire from top to bottom, and use a blower to blow high-temperature air from bottom to top into the bottom of the copper wire to obtain a primary copper sulfate electrolyte; after filtering the primary copper sulfate electrolyte, add additive 1 and mix to obtain a secondary electrolyte; the secondary electrolyte is maintained at a temperature of 48° C. through a heat exchanger, and is transported to a high-level tank and mixed evenly with the additive 2 solution to obtain an electrolyte, and the electrolyte is pumped into an electrolytic cell for electrolysis.

[0046] Step 2: Electrolytic preparation of green foil: at 48°C and 60A / dm 2 The raw foil is prepared by electrolysis in an electrolytic cell at a current density of .

[0047] Step 3, raw foil surface treatment: The prepared raw foil is subjected to conventional passivation treatment to obtain uncut finished electrolytic copper foil for lithium batteries. The passivation solution used in the conventional treatment contains 110 mg / L chromic anhydride, 220 mg / L glucose and RO water, the pH of the passivation solution is 3.4, the passivation treatment temperature is 30°C, and the passivation treatment current is 2A / dm 2 .

[0048] Example 3 An electrolyte for electrolytic copper foil

[0049] Includes the following components: 110g / L Cu 2+ , 130g / L H2SO4, additive 1, additive 2 and solvent water.

[0050] The additive 1 includes 1.0 mg / L of Cl - , 50mg / L Ni 2+ and solvent; the Cl - is hydrochloric acid, Ni 2+ It is nickel sulfate hexahydrate.

[0051] The additive 2 includes: 26 mg / L sodium polydisulfide propane sulfonate, 13 mg / L sodium N,N-dimethyl-dithiocarboxamide propane sulfonate, 13 mg / L sulfonamide, 52 mg / L gelatin (molecular weight 10000-50000 Da), 26 mg / L hydroxyethyl cellulose, 26 mg / L polyethylene glycol and a solvent.

[0052] The production process of the above electrolyte for producing 6μm high elongation electrolytic copper foil for lithium batteries is as follows:

[0053] Step 1, preparation of electrolyte: copper powder is placed in a copper dissolving tank, sulfuric acid is added from the top of the copper powder from top to bottom, and high-temperature air is blown from the bottom to top by a blower to obtain a primary copper sulfate electrolyte; the primary copper sulfate electrolyte is filtered, and additive 1 is added and mixed to obtain a secondary electrolyte; the secondary electrolyte is maintained at a temperature of 52° C. through a heat exchanger, and is transported to a high-level tank and mixed evenly with the additive 2 solution to obtain an electrolyte, and the electrolyte is pumped into an electrolytic cell for electrolysis.

[0054] Step 2: Electrolytic preparation of green foil: at 52°C and 70A / dm 2 The raw foil is prepared by electrolysis in an electrolytic cell at a current density of .

[0055] Step 3, raw foil surface treatment: The prepared raw foil is subjected to conventional passivation treatment to obtain uncut finished electrolytic copper foil for lithium batteries. The passivation solution used in the conventional treatment contains 110 mg / L chromic anhydride, 220 mg / L glucose and RO water, the pH of the passivation solution is 3.4, the passivation treatment temperature is 35°C, and the passivation treatment current is 2A / dm 2 .

[0056] Comparative Example 1: An electrolyte for electrolytic copper foil

[0057] The difference from Example 1 is that:

[0058] Additive 1 includes 0.5 mg / L Cl - and solvent water, Ni-free 2+ .

[0059] Comparative Example 2: An electrolyte for electrolytic copper foil

[0060] The difference from Example 1 is that:

[0061] Additive 2 includes 26 mg / L sodium polydisulfide propane sulfonate, 10 mg / L sodium N,N-dimethyl-dithiocarboxamide propane sulfonate, 4 mg / L sulfonamide, 40 mg / L gelatin (molecular weight 10000-50000 Da), 20 mg / L hydroxyethyl cellulose, 20 mg / L polyethylene glycol and a solvent.

[0062] Comparative Example 3: An electrolyte for electrolytic copper foil

[0063] The difference from Example 1 is that:

[0064] Additive 2 includes: 26 mg / L sodium polydisulfide propane sulfonate, 13 mg / L sodium N,N-dimethyl-dithiocarboxamide propane sulfonate, 13 mg / L sulfonamide, 52 mg / L gelatin (molecular weight 10000-50000 Da), 26 mg / L hydroxyethyl cellulose, 26 mg / L polyethylene glycol and solvent.

[0065] Effect example

[0066] The physical properties of the electrolytic copper foils produced in the embodiments of the present invention and the comparative examples were tested, and the results shown in Table 1 were obtained.

[0067] The cross sections of the electrolytic copper foils of the embodiment and the comparative example were subjected to electron backscatter diffraction (EBSD) testing. The BC diagram and IPF diagram of the cross sections of the samples were as follows: Figure 1-Figure 6 The cross section of the electrolytic copper foil of the embodiment of the present invention has dense crystals, small and uniform grain size, no obvious texture, and no transition layer.

[0068] Table 1 Physical properties of electrolytic copper foil

[0069]

[0070] In summary, the electrolytic copper foil prepared by the electrolyte of the present invention can obtain uniform, dense and fine grains, and effectively inhibit the generation of the transition layer of the electrolytic copper foil. The room temperature tensile strength and elongation of the electrolytic copper foil prepared by the electrolyte of the present invention meet the standards, and the warpage is ≤10mm.

[0071] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. An electrolyte for electrolytic copper foil, characterized in that: Including Cu 2+ 90g / L, 110g / L H2SO4, 1.5mg / L Cl - , 60mg / L Ni 2+ , sodium polydisulfide propane sulfonate 24 mg / L, sodium N,N-dimethyl-dithiocarboxamide propane sulfonate 12 mg / L, sulfonamide 12 mg / L, gelatin 48 mg / L, hydroxyethyl cellulose 24 mg / L, polyethylene glycol 24 mg / L and solvent; or Cu 2+ 110g / L, H2SO4130g / L, Cl - 1.0mg / L、Ni 2+ 50mg / L, sodium polydisulfide propane sulfonate 26mg / L, sodium N,N-dimethyl-dithiocarboxamide propane sulfonate 13mg / L, sulfonamide 13mg / L, gelatin 52mg / L, hydroxyethyl cellulose 26mg / L, polyethylene glycol 26mg / L and solvent.

2. The electrolyte according to claim 1, characterized in that: The Cu 2+ The raw material is copper wire, copper rod, copper block or copper powder; the solvent is ultrapure water.

3. The electrolyte according to claim 1, characterized in that: The Cl - The raw material is hydrochloric acid; the Ni 2+ The raw material is at least one of nickel sulfate hexahydrate, nickel chloride hexahydrate, nickel oxide and nickel hydroxide.

4. The electrolyte according to claim 1, characterized in that: The molecular weight of the gelatin is 10000Da-50000Da.

5. The method for preparing the electrolyte according to any one of claims 1 to 4, characterized in that: Including Cu 2+ The raw materials react with H2SO4 to obtain a primary copper sulfate electrolyte, which is then filtered and mixed with Cl - Raw materials and Ni 2+ The raw materials are mixed to obtain a secondary electrolyte, which is then maintained at a high temperature and mixed with sodium polydisulfide propane sulfonate, sodium N,N-dimethyl-dithiocarboxamide propane sulfonate, sulfonamide, gelatin, hydroxyethyl cellulose, and polyethylene glycol to obtain the electrolyte.

6. Use of the electrolyte according to any one of claims 1 to 4 or the electrolyte prepared by the preparation method according to claim 5 in preparing electrolytic copper foil for lithium batteries.

7. An electrolytic copper foil, characterized in that: Prepared from the electrolyte according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Composite additive for ultra-thin electrolytic copper foil with ultra-high tensile strength and electrolytic copper foil preparation method applying additive

    CN116180164A

  • Method for manufacturing electrolytic copper foil

    KR102405236B1